GIS-material for the archaeological project: Hulterstad property - New road on Hulterstad property - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned road construction the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation in May 2005 with the Hulterstad property. The road stretches through a potential settlement location and nearby a hill fort. No features or finds were discovered during the trial trenching. UV Öst suggests no further archaeological measures.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to delimit the protected area around the hill fort site RAÄ 173 and also to determine whether there are any prehistoric settlement remains on the height west of the hill fort. If any remains were found, their type, intensity and, if possible, dating was to be determined.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har i maj 2005 genomfört en arkeologisk förundersökning inom Hulterstad egendom, med anledning av en planerad väg. Vägen sträcker sig genom ett lämpligt boplatsläge och i närheten av en fornborg. Vid sökschaktsgrävning påträffades inga fynd eller anläggningar. UV Öst föreslår att inga ytterligare antikvariska åtgärder behövs.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var dels att begränsa fornlämningsområdet tillhörande fornborgen RAÄ 173. Dels var syftet att konstatera om det finns förhistoriska boplatslämningar på höjdpartiet väster om fornborgen. Om lämningar framkom skulle dessas art och intensitet konstateras och om möjligt dateras.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Hulterstad egendom - Ny väg inom Hulterstad egendom
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive